Impact of social and psychological factors on academic achievement of university students - Amela Džubur; Delila Lisica; Damir Abdulahović; Malik Ejubović (Medicinski glasnik, 2019)
Aim: To examine the correlation between personality traits, learning styles, and academic achievement and a difference between students' gender, residency status and academic achievement. Methods: The study included 95 students of first year of the School of Medicine, University of Sarajevo. The survey used the sociodemographic questionnaire, Index of Learning Style and Big Five Inventory. Academic achievement was represented by a cumulative grade point of each student. Results: There was significant difference between the students' gender, information processing style, i.e. active/reflective learning style and academic achievement. Academic achievement was correlated with extraversion (negatively), conscientiousness and active/reflexive learning style. Conclusion: With this study we wanted to improve awareness of teachers about the importance and use of different styles during lecture, to show the importance of students knowing their own preferences and learning styles, and how personality traits can affect students' academic achievement. Academic performance is an important outcome for students. It can increase motivation, student participation in class and wish to volunteer in different activities.
Keywords: learning styles; performance; personality traits; residency